Med odrom in zaodrjem - Bogunović Hočevar, Katarina (Muzikološki zbornik, 2023)
The article sheds light on the first years of operation of the Opera National Theatre in Ljubljana after the First World War. Based on available sources, it partially reconstructs the organisational structure and artistic interrelation of the institution. In the absence of primary sources or documentation revealing the inner life of the opera ensemble, the article relies on everyday critical testimonies of the musical protagonists of the time.
Keywords: 1918-1922; Juvančič, Friderik; Kogoj, Marij; Opera; Opera Narodnega gledališča v Ljubljani; Opera National Theater in Ljubljana; Rukavina, Friderik; Slovene music; slovenska glasba; Slovenski gledališki konzorcij; Theatre Consortium